2015
DOI: 10.3389/fnbeh.2015.00003
|View full text |Cite
|
Sign up to set email alerts
|

FRIEND Engine Framework: a real time neurofeedback client-server system for neuroimaging studies

Abstract: In this methods article, we present a new implementation of a recently reported FSL-integrated neurofeedback tool, the standalone version of “Functional Real-time Interactive Endogenous Neuromodulation and Decoding” (FRIEND). We will refer to this new implementation as the FRIEND Engine Framework. The framework comprises a client-server cross-platform solution for real time fMRI and fMRI/EEG neurofeedback studies, enabling flexible customization or integration of graphical interfaces, devices, and data process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Our study employed a freely available rt-fMRI software (FRIEND 6 ; Sato et al, 2013 ; Basilio et al, 2015 ). This may contribute for expansion of the NFB fMRI use and allow a better comparability across studies, which is fundamental for future applications in clinical research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study employed a freely available rt-fMRI software (FRIEND 6 ; Sato et al, 2013 ; Basilio et al, 2015 ). This may contribute for expansion of the NFB fMRI use and allow a better comparability across studies, which is fundamental for future applications in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…During MI (“GO” blocks), participants received either real NFB or random visual stimuli. Continuous online neurofeedback data was performed using FRIEND (Functional Real-time Interactive Endogenous Neuromodulation and Decoding) toolbox 1 ( Sato et al, 2013 ; Basilio et al, 2015 ), which is a home-built toolbox for fMRI NFB. First, a linear registration between the EPI image (RFI) and a MNI template brain was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…html; Weiskopf et al, 2004), a BioImageSuite extension (bisweb. yale.edu; Scheinost et al, 2013a), a FSL based toolbox, FRIEND (nitrc.org/projects/friend/; Sato et al, 2013;Basilio et al, 2015), and an SPM/Matlab based toolbox OpenNFT (opennft.org; Koush et al, 2017). Many groups use custom implementations or extensions of these toolboxes and plugins.…”
Section: Artifacts and Technical Problemsmentioning
confidence: 99%
“…the spiral-in/out sequence by Glover and Law, 2001), only 1 study from the 128 reported incorporating postacquisition distortion correction into their real-time algorithm (Marxen et al, 2016). Although open source software solutions like AFNI's real-time plugin (Cox et al 1995), BART (Hellrung et al, 2015), FRIEND (Basilio et al, 2015) and OpenNFT counter some of these concerns, we find additionally that minimal evidence exists for open data and methods sharing. Specifically, apart from a large dataset on default-modenetwork neurofeedback shared publicly by McDonald et al 2017, and further useful supplementary data shared in some cases (e.g.…”
Section: Denoising In Real-time Fmri Neurofeedback Studiesmentioning
confidence: 81%
“…Most other rtfMRI-NF toolboxes or custom software implementations allow some form of 3D volume realignment, e.g. OpenNFT which uses a faster version of SPM12's spm_realign routine (SPM, www.fil.ion.ucl.ac.uk/spm), or FRIEND (Basilio et al, 2015) that incorporates FSL's MCFLIRT algorithm (FSL, https://fsl.fmrib.ox.ac.uk/fsl).…”
Section: D Volume Realignmentmentioning
confidence: 99%